Making Supply Chain Management Work: Design, Implementation, Partnerships, Technology, and Profits - Ayers, James (CRC Press, 2009)
Any supply chain improvement project, even if well conceived, has a good chance of failing, unless the accompanying information technology enables the design. Being prepared, understanding the risks and how to reduce them, will give you the edge you need. Combining a technology focus with practical advice, Making Supply Chain Management Work: Design, Implementation, Partnerships, Technology, and Profits gives you the tools to not only design new supply chains, but to design them effectively.